Increasing sustainable consumption: message framing and in-store technology. Issue 8 (26th May 2020) - Jäger, Anna-Katharina; Weber, Anja
Abstract : Purpose: This study investigates the potential of two different digital in-store technologies and advertisement message framings according to the construal-level theory for increasing sustainable consumption. This paper aims to provide managerial implications for the promotion of sustainable products at the point of sale as well as to theoretically contribute by integrating the literature streams of perceptual research, point-of-sale marketing and construal-level theory. Design/methodology/approach: The authors tested their hypotheses in a two-week field experiment with a 2 (product label: organic vs local) × 2 (message framing: high vs low construal level) × 2 (presentation technology: digital signage vs augmented reality) between-subjects factorial design. The study was conducted in two grocery stores of different sizes using milk as a test product. Purchase data, as well as attention data gathered by facial recognition software, were analyzed. Findings: Even though the magic mirror augmented reality application attracted significantly more attention, it did not significantly boost sales compared to the digital signage technology. In the larger store, the sales of the advertised sustainable products were significantly higher in both technology conditions than in the control condition without advertisement. If consumers pay enough attention to the promotion, results indicate that using messages with a concrete low-level construal is more useful for organic goods. Originality/value: This study is the first investigating a combination of in-store technology and construal-level message framing for the promotion of sustainable products. It extends the retailing literature by proposing a two-step approach on how to use in-store technology effectively: (1) gaining attention and (2) matching messages to existing cognitions.